PEMBERDAYAAN POKLAHSAR SEKAR TAJI MELALUI DIVERSIFIKASI PRODUK PERIKANAN BERBASIS ZERO WASTE - Nazizah, Fitrotin; Nurmalasari, Yanti; Ekalaturrahmah, Yenni Arista Cipta (Universitas Mataram, 2024)
The problem of Poklahsar Sekar Taji is the low added value of fishery products produced and unused fish waste, which hampers the potential of fisheries in the South Candi Hamlet area, Polagan Village, Galis District, Pamekasan Regency. The purpose of this service activity is to empower Poklahsar Sekar Taji through training on fish diversification processing based on Zero waste, including the processing of fish bone meal and fish bone crackers. The implementation method is socialization, training and evaluation of post-training activities. The result of this service activity is to be able to improve the knowledge and skills of partners in processing fish bone meal and fish bone crackers. The increase in knowledge and skills can be seen in the Pre Test and Post Test scores where 74% there is an increase in the knowledge and skills of partners related to Zero Waste-based fisheries diversification processing. This activity succeeded in increasing the processing capacity of value-added and environmentally friendly fishery products, as well as having a positive impact on local economic and environmental welfare.